اجراءات تحسين إنتاجية القطاع الفلاحي في الجزائر دراسة تحليلية لدعم الري الفلاحي للفترة : 2000-2016 (Revue El-Wahat pour les Recherches et les Etudes, 2021)
ملخص:تحاول هذه الدراسة معرفة مدى تأثير مختلف اشكال الدعم الإنتاجي والتقني على القطاع الزراعي في الجزائر وخاصة اهم اجراءات تنمية الري الفلاحي خلال فترة الاستثمارات العامة الممتدة من 2000-2016 ومن خلال الدراسة القياسية التحليلية التي حاولت معرفة مدى تأثير استهلاك الرأسمال الثابت والدعم المالي الفلاحي على الانتاج الزراعي فقد لاحظنا التأثير المحتشم لهما والذي لا يرقى الى الاهداف المرجوة، ومن هذا المنطلق من واجب الدولة بعد الاهتمام بمدخلات الإنتاج من رأسمال والأرض وعامل التكنولوجيا التوجه نحو الاهتمام بمدخل مهم وهو التنظيم فان التقدم التقني والمخصصات المالية يجب أن تكون مقرونة بإدارة تقنية فعالة لتحسين إنتاجية هذاالقطاع  الكلمات الدالة:التطور التقني, تحسين الإنتاجية, تنمية الري الفلاحي.   Abstract: This study attempts to know the extent of the impact of various forms of productive and technical support on the agricultural sector in Algeria, especially the most important measures to develop agricultural irrigation during the public investment period extending from 2000-2016, And through the analytical standard study that tried to know the extent of the impact of consumption of fixed capital and agricultural financial support on agricultural production, we have noticed the modest effect of them, which does not rise to the desired goals, From this standpoint, it is the duty of the state, after paying attention to production inputs from capital, land, and the technology factor to pay attention to an important input, which is regulation, so technical progress and financial allocations must be coupled with effective technical management to improve the productivity of this sector Key words: Technical development, productivity improvement, agricultural irrigation development.